2017
DOI: 10.12691/jfa-5-3-2
|View full text |Cite
|
Sign up to set email alerts
|

Fiscal Synchronisation or Institutional Separation: An Examination of Tax-Spend Hypothesis in Nigeria

Abstract: This paper investigates the position of Nigeria within the various fiscal hypotheses (tax-spend, spend-tax, fiscal synchronization and fiscal neutrality hypotheses) using Granger Causality and Block Exogeneity Wald Test within the framework of Vector Error Correction (VEC) Model. The study established one-directional causality that runs from revenue to expenditure (Tax-Spend Hypothesis). This suggests that current government effort at increasing tax revenue is a positive development to reduce or revert the eco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 19 publications
1
1
1
Order By: Relevance
“…However, our results supporting the spend-and-tax hypothesis are inconsistent with the studies of Vamvoukas (2012), Akram and Rath (2019), and Jaén-García (2020), who found empirical evidence on the fiscal synchronization hypothesis, and Yinusa and Adedokun (2017), Gurvich and Krasnopeeva (2020) and Tashevska et al (2020), who found empirical evidence on the tax-and-spend hypothesis. The contradictory results of empirical studies may have arisen from the circumstance contingent characteristics of the tax-spend relationship that could vary depending on the countries’ economic environments and also institutional structures.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…However, our results supporting the spend-and-tax hypothesis are inconsistent with the studies of Vamvoukas (2012), Akram and Rath (2019), and Jaén-García (2020), who found empirical evidence on the fiscal synchronization hypothesis, and Yinusa and Adedokun (2017), Gurvich and Krasnopeeva (2020) and Tashevska et al (2020), who found empirical evidence on the tax-and-spend hypothesis. The contradictory results of empirical studies may have arisen from the circumstance contingent characteristics of the tax-spend relationship that could vary depending on the countries’ economic environments and also institutional structures.…”
Section: Resultscontrasting
confidence: 99%
“…Magazzino (2013), also found empirical evidence in favor of the tax-and-spend hypothesis in Gambia, Liberia, Nigeria, and Sierra Leone. Additionally, Yinusa and Adedokun (2017) and Gurvich and Krasnopeeva (2020) also found supportive evidence for tax-and-spend hypothesis in Nigeria and Russia, respectively. As opposed to supportive studies for the tax-and-spend hypothesis, Lusinyan and Thornton (2012), applied the Granger Causality test to data from the United Kingdom for the period of 1750 to 2014 and found that the government spendings granger caused tax revenues which means spend-and-tax hypothesis was in effect in the United Kingdom for the selected period.…”
Section: Literature Reviewmentioning
confidence: 61%
“…Firstly, the earn-and-spend hypothesis (or tax-spend, or revenue dominance hypothesis) proposed by Buchanan and Wagner (1977) and Friedman (1978) argue the existence of a unidirectional causality flow from government revenue to government expenditure. Similar studies have also confirmed this hypothesis , Yinusa and Adedokun (2017) in Nigeria; Rezaei (2015) in Iran; Sahed et al (2020) in Algeria). Secondly, the spend-and-earn hypothesis (or spend-tax or expenditure dominance hypothesis) led by Wiseman (1961, 1979) states that there is a unidirectional causality from government expenditures to revenue.…”
Section: Introductionsupporting
confidence: 70%
“…Government has spent more than 70 percent of its budgetary allocations on recurrent expenditure which was mainly used in servicing politicians' demand through their jumbo allowances and salaries (see El-rufai, 2011). It can be deduced that increase in the level of economic growth has a direct correlation with expansion in government spending as theorized by Wagner (1883). Thus, it can be said that the overall performance of Nigerian economy is not impressive despite large budgetary allocations over the years.…”
Section: Stylized Facts On Economic Growth and The Size Of Public Exp...mentioning
confidence: 99%
“…Accordingly, the analytical technique used and the classification of public spending, and data used contributed to the inconsistent findings, hence, the need for this study. Wagner (1883) was the first economist that theorized the influence of level of economic growth and development on public sector expansion. Since his pioneering work in 1883, volume of empirical studies have studied the nexus between economic growth and public expenditure with mixed findings (see Barro, 1990;Folster & Henrekson, 2001;Forte & Magazino, 2016;Grossman, 1988;Mackness, 1999;Peden & Bradley, 1989).…”
Section: Empirical Reviewmentioning
confidence: 99%